New or little-known species of Chaetocladius s. str. Kieffer, 1911 (Diptera: Chironomidae: Orthocladiinae) from the Amur River basin (Russian Far East) - Makarchenko, Eugenyi A.; Makarchenko, Marina A.; Semenchenko, Alexander A. (Zootaxa, 2017)
Chironomids of the subgenus Chaetocladius s. str. from the Amur River basin are revised using both morphological characters and molecular data. Three new species, C. egorych sp. nov., C. lopatinskiy sp. nov. and C. yavorskayae sp. nov., are described and figured. The pupa of C. fedotkin is described for the first time. Adult males of C. ligni and C. piger, little-known in the Far East, are redescribed and annotated, and key to males of the Chaetocladius s. str. from the Amur River basin is provided. A reference 658 bp barcode sequence from a fragment of the mitochondrial gene cytochrome oxidase I (COI) was used as a tool for species delimitation. Comparisons with corresponding regions of COI between 5 species in the subgenus produced K2P genetic distances of 8.3–12.6%, values well associated with interspecific variation. Molecular data were also used for the reconstruction of the phylogenetic relationships within the subgenus Chaetocladius s. str.